Penerapan Strategi Diescovery Learning Mata Pelajaran Fikih Siswa Kelas VII MTS Al Hidayah Sei Tualang Kecamatan Brandan Barat - Mardiana, Syahrul Qodrah, Marhan Hasibuan (Pusdikra Publishing, 2023)
The research method used in this research is descriptive qualitative to describe and describe the implementation of the Discovery Learning learning model in fiqh subjects at MTs Al Hidayah Sei Tualang. The subjects of this research are students of class VII MTs Al hidayah Sei Tualang in the 2022/2023 school year totaling 26 people, teachers teaching fiqh subjects, and all components that are part of this research. In this study, the techniques used to collect data in this study were observation, interviews, and documentation. The results showed that the application of the diescovery learning method begins with determining the objectives of the fiqh material, the teacher plans the learning with the form of learning designs such as syllabus and lesson plans. Furthermore, the teacher provides stimulation by asking questions and problems about the phenomena that occur around. the teacher tells students to search for data that is in accordance with the problem which is then discussed with friends. and proven the truth through the teacher's explanation, the last teacher conducts an assessment of the final results of student learning conclusions. The application of the discovery learning method has a positive impact on students because in its application students get a lot of experience and also new knowledge directly because fiqh learning material is religious practice in everyday life. Factors that support the implementation of Discovery Learning Based on fiqh learning at MTs Al Hidayah Sei Tualang are two factors, namely internal and external factors. Internal factors are student intelligence and student enthusiasm in learning. While the external factors are teachers, social conditions, infrastructure and provision of rewards or awards. As for the inhibiting factors from the implementation of learning, there are several factors that hinder the application of learning methods, including the condition of large classes that tend to have many students and are crowded when the teacher provides stimulation at the beginning of learning. In addition, it is also constrained by the condition of inadequate infrastructure so that the application of the diescovery learning method is carried out with media made by teachers with their respective creativity, and in its application the diescovery learning method is also carried out outside the classroom so that the time used is not enough.